Nusantara Queen Genealogy: History, Myths and Modern State Politics - Sugiarto, Ryan (Yayasan Jurnal Perempuan, 2014)
Genealogy and history of queens in Nusantara had been written in golden ink. Their histories across Nusantara were not only an accumulation of wives or ruler, but also inhibited the magic-realism of modern Indonesian society. However, the minimum or rare documents of Nusantara’s women leadership had blurred their real representation and strong leadership. This paper investigates the history, roles, status and profiles of women’s leader. This paper aims to support current political situation specifically on the tradition of writing woman’s her-stories. From this perspective legitimacy of power from history are taken to support women’s leadership in current modern Indonesia state.